From the war in youth to the trauma of defeat, repression and exile. Images and discourses of Spanish Republican aviation - Carmen Marimón Llorca; Juan Antonio Roche Cárcel (Cogent Arts & Humanities)
The Spanish Civil War (1936-1939) was a cruel confrontation whose consequences were aggravated by Franco’s repression. One army corps that represents the suffering and, at the same time, the will for individual and collective recovery at its best is the Republican air force. The airmen lost the war, their profession and democracy, and those who survived the conflict, the dictatorship, repression and exile experienced what can be described as collective trauma. The aim of this work is to show the nature of this trauma through the analysis of a set of photographic images -more than 2000- from the documentary collection of the Archive of Democracy of the University of Alicante and ADAR (the Association of Aviators of the Republic). Their analysis has allowed us to gather them into three groups: youth and war; defeat, repression and exile; memory and forgiveness. The description of the images carried out using the methodology of iconological analysis is reinforced with texts from ADAR bulletins and biographical and autobiographical works by the aviators. Both discursive expressions, linguistic and photographic, reinforce the experiential account of this group and the trauma they experienced.